Construction of Magnetocarried Nanocomposites for Medico-Biological Applications - Gorbyk, P.P.; Petranovska, A.L.; Turelyk, M.P.; Abramov, N.V.; Chekhun, V.F.; Lukyanov, N.Yu. (Хімія, фізика та технологія поверхні, 2010)
The research work deals with studies on interactions of nanomaterials with components of biosystems, development of new medicines based on magnetite, their application efficiency, chemical engineering of multilevel magnetosensitive nanocomposites with a hierarchical architecture and functions of biomedical nanorobots.